Emerging Economies, Trade Policy, and Macroeconomic Shocks - Bown, Chad P.; Crowley, Meredith A. (World Bank, Washington, DC, 2013)
This paper estimates the impact of aggregate fluctuations on the time-varying trade policies of 13 major emerging economies over 1989-2010. By 2010, these World Trade Organization member countries collectively accounted for 21 percent of world merchandise imports and 22 percent of world gross domestic product. The paper examines determinants of carefully constructed, bilateral measures of new import restrictions on products arising through the temporary trade barrier (TTB) policies of antidumping, safeguards, and countervailing duties. The approach explicitly addresses changes to the institutional environment facing these emerging economies as they joined the WTO and adopted disciplines to restrain their application of other trade policies, such as applied import tariffs. The paper presents evidence of a counter-cyclical relationship between macroeconomic shocks and new TTB import restrictions in addition to an important role for fluctuations in bilateral real exchange rates. Furthermore, for the subset of major Group of 20 emerging economies, the trade policy responsiveness coinciding with WTO establishment in 1995 suggests a significant change relative to the pre-WTO period; i.e., new import restrictions became more counter-cyclical over time. Finally, the paper documents evidence on changes to some of these empirical relationships coinciding with the Great Recession.